2023
DOI: 10.3390/cancers15092444
|View full text |Cite
|
Sign up to set email alerts
|

Taxane-Induced Neuropathy and Its Ocular Effects—A Longitudinal Follow-up Study in Breast Cancer Patients

Abstract: A common severe neurotoxic side effect of breast cancer (BC) therapy is chemotherapy-induced peripheral neuropathy (CIPN) and intervention is highly needed for the detection, prevention, and treatment of CIPN at an early stage. As the eye is susceptible to neurotoxic stimuli, the present study aims to determine whether CIPN signs in paclitaxel-treated BC patients correlate with ocular changes by applying advanced non-invasive biophotonic in vivo imaging. Patients (n = 14, 10 controls) underwent monitoring sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Ocular neurotoxicity has been hypothesised as neurotoxicity in two small studies. One study found increased retinal thickness in taxaneexposed ESBC patients (137), and another found worse ocular discomfort in patients with TIPN compared to BC survivors without TIPN (138).…”
Section: Other Taxane -Induced Neurotoxicitymentioning
confidence: 99%
“…Ocular neurotoxicity has been hypothesised as neurotoxicity in two small studies. One study found increased retinal thickness in taxaneexposed ESBC patients (137), and another found worse ocular discomfort in patients with TIPN compared to BC survivors without TIPN (138).…”
Section: Other Taxane -Induced Neurotoxicitymentioning
confidence: 99%